Non-stationarity in Southern Hemisphere climate variability associated with the seasonal breakdown of the stratospheric polar vortex - Byrne, N; Shepherd, T; Woollings, T; Plumb, R (American Meteorological Society, 2017)
Statistical models of climate generally regard climate variability as anomalies about a climatological seasonal cycle, which are treated as a stationary stochastic process plus a long-term seasonally dependent trend. However, the climate system has deterministic aspects apart from the climatological seasonal cycle and long-term trends, and the assumption of stationary statistics is only an approximation. The variability of the Southern Hemisphere zonal-mean circulation in the period encompassing late spring and summer is an important climate phenomenon and has been the subject of numerous studies. It is shown here, using re-analysis data, that this variability is rendered highly non-stationary by the organizing influence of the seasonal breakdown of the stratospheric polar vortex, which breaks time symmetry. It is argued that the zonal-mean tropospheric circulation variability during this period is best viewed as interannual variability in the transition between the springtime and summertime regimes induced by variability in the vortex breakdown. In particular, the apparent long-term poleward jet shift during the early-summer season can be more simply understood as a delay in the equatorward shift associated with this regime transition. The implications of such a perspective for various open questions are discussed.